The spirit of Muslim culture according to Muhammad Iqbal - Abdul Rahim, Adibah (International Association of Computer Science and Information Technology Press (IACSIT), 2015)
In the history of civilization, culture and religion have always developed in a close proximity to each other. Indeed, one cannot conceive of development in religion and culture in isolation from each other. it is precisely this unity of culture and religion which is to be the basis of Muhammad Iqbal's views on Muslim culture. Culture, for Iqbal,is the most important factor of sociological life and the basis of its change. In explaining social change, he believed that culture plays a greater role than other factors, such as, economy and politics. Although he has deeply studied the Western thought, Iqbal's views on culture are essentially shaped by the teachings of the Qur'an. This paper tries to explore Iqbal's concept of Muslim culture and its spirit. it does not mainly concern with the determination of what constitutes culture or the enumeration of various traits of Muslim culture. rather, the paper tries to study Iqbal's critical evaluation of the spirit of Muslim culture and the fundamental principles which motivate, inspire, and direct Muslims in their cultural pursuits.